Fly Ash/Silica Fume Coral Concrete with Modified Polypropylene Fiber for Sustainable Building Construction - Bo Wang; Wenhao Shi; Qing Wu; Xun Xi; Shangtong Yang (Advances in Civil Engineering)
Coral concrete made of coral sand/aggregates has attracted significant interest in the construction of coastal or artificial island buildings by saving significant economic and environmental costs for transporting the conventional building materials from mainland. However, the application of coral concrete is very limited due to the drawback such as low strength, brittleness, and high porosity. This paper develops a new coral concrete composite utilizing coral debris to replace sand and aggregates, sea water, supplementary cementitious waste materials, namely, fly ash and silica fume and modified polypropylene fiber (MPPF) to achieve both sustainable and economic development needs in coastal and island building and construction. The mechanical and durability of the new coral concrete are evaluated and the synergistic effects of fly ash and silica fume on the performance of MPPF coral concrete are discussed. It has been found out that the addition of fly ash and silica fume in MPPF coral concrete can significantly improve the strengths and reduce the chloride diffusion of coral concrete. Compared with those from the specimens without fly ash and silica fume, the compressive, splitting tensile, flexural strengths of MPPF concrete with 10% fly ash and 10% silica fume are improved by 31%, 33%, and 58%, respectively. The new coral concrete composite would be an ideal building material solution for coastal and artificial island applications as most of the materials come from the local wastes.